Kesulitan Belajar Akuntansi Keuangan (Studi Kasus Pada Materi Merchandise Inventory Management) - Zuhri Saputra Hutabarat (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2022)
This study aims to identify and obtain an overview, data and information that are considered important about learning difficulties in financial accounting subjects (intermediate) on merchandise inventory management materials. In accordance with the methodology this research is a qualitative research, the research uses the condition of the natural object of the researcher as a key instrument in triangulating data collection in induced data analysis so that it places more emphasis on generalized meanings. The factors that cause learning difficulties in various ways are as follows: 1) Lack of student understanding in studying financial accounting subjects (intermediate) on merchandise inventory management materials, 2) Materials in identifying and recording inventory cards using two recording systems merchandise, 3) In recording the valuation of merchandise inventory to find the total cost of goods sold and the total value of the ending inventory using the five methods and 4) At the end of the accounting period, make a report on the inventory of merchandise.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//